ANALISIS KOMPARATIF TENTANG KOMITMEN WAJIB PAJAK DALAM MELAPORKAN SURAT PEMBERITAHUAN (SPT) PAJAK PADA PERHOTELAN DAN RESTORAN DI SEMARANG - Prista Dilasari, Aranta (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2018)
The problem raised in this study is the commitment of the Tax Return Annual Report (SPT) based on the RI Taxation Law No. 36 of 2008 Article 17 of hotels and restaurants. This study uses a combined approach, which is operationally trying to qualify quantitative results and quantify qualitative results, where the results will be measured based on research indicators for each data group. Furthermore, it was measured using an analysis of the t test (independent sample test) separated variance to get the results of the comparison between the tax return reporting commitment from hospitality with restaurants. The results showed that most of the hotels had high commitments, but there were still 18 companies that were in the Low and Very Low categories. Whereas in most restaurants the number of companies has a high commitment, but there are still 5 companies that have the category of Low and Very Low. The tax return reporting commitment between hospitality and restaurants has a significant difference.